Sudangrass, sorghum-sudan, forage sorghum, and corn silages and three protein levels for growing yearling steers - W. Thompson; J. Oltjen; K. Bolsen; H. Ilg; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1978)
Sudangrass, sorghum-sudan, forage sorghum, and corn silages were full-fed to yearling steers for 70-or 91-day growing periods. For both periods, steers fed corn silage outperformed steers fed any other silage. In the 70-day period silages from both sudangrass and sorghum-sudan cut at 45- and 60-inch plant heights, respectively, supported performance similar to forage sorghum silage. For both periods steers fed sorghum-sudan (dough) silage gained slowest and least efficiently. For the 91-day period, rations containing 12.0% crude protein supported better performance than rations containing 10.5 or 9% protein and 10.5% protein rations supported better performance than 9% protein rations.
Keywords: Cattlemen& #x27; s Day; 1978; Report of progress (Kansas State University. Agricultural Experiment Station); 320; Beef; Sudangrass; Sorghum-sudangrass; Forage sorghum; Corn silage; Protein; Steers